Roles of reactive oxygen species, mitochondrial membrane potential, and p53 in evodiamine-induced apoptosis and G2/M arrest of human anaplastic thyroid carcinoma cells - Chih-Chiang Chien; Ming-Shun Wu; Shih-Wei Chou; Ganbolor Jargalsaikhan; Yen-Chou Chen (Chinese Medicine, 2021)
Abstract Background Our previous studies have shown that evodiamine (EVO) as paclitaxel and nocodazole could trigger apoptosis in various human cancer cells including human renal cell carcinoma cells, colorectal carcinoma cells, and glioblastoma cells. This study aims to investigate the anti-cancer effects of EVO on human anaplastic thyroid carcinoma (ATC) cells, and underlining mechanism. Methods Two different endogenous p53 status human anaplastic thyroid carcinoma (ATC) cells including SW1736 (wtp53) and KAT4B (mutp53) were applied in the present study. The cytotoxicity of EVO on ATC cells was measured by MTT assay, and apoptosis and G2/M arrest were detected by propidium iodide (PI) staining followed by flow cytometry. Expression of indicated proteins was evaluated by Western blotting analysis, and pharmacological studies using chemical inhibitors and siRNA were performed for elucidating underlying mechanism. The roles of mitochondrial membrane potential and reactive oxygen species were investigated by flow cytometry using DiOC6 and DCFH-DA dye, respectively. Results SW1736 (wtp53) cells showed a higher apoptotic percentage than KAT4B (mutp53) cells in response to EVO stimulation via a flow cytometric analysis. Mechanistic studies showed that increased p53 and its downstream proteins, and disrupted MMP with increased intracellular peroxide production participated in EVO-induced apoptosis and G2/M arrest of SW1736 cells. In EVO-treated KAT4B cells, significant increases in G2/M percentage but little apoptotic events by EVO was observed. Structure-activity analysis showed that an alkyl group at position 14 was critical for induction of apoptosis related to ROS production and MMP disruption in SW1736 cells. Conclusion Evidence indicated that the endogenous p53 status affected the sensitivity of ATC cells to EVO-induced apoptosis and G2/M arrest, revealing the potential role of p53 related to increased ROS production and disrupted MMP in the anticancer actions of EVO, and alkylation at position 14 of EVO is a critical substitution for apoptosis of ATC cells.